Population‐based study of morbidity risk associated with pathological complete response after chemoradiotherapy for rectal cancer. Issue 1 (17th October 2019) - van der Sluis, F. J.; Couwenberg, A. M.; de Bock, G. H.; Intven, M. P. W.; Reerink, O.; van Leeuwen, B. L.; van Westreenen, H. L.
Abstract : Background: Neoadjuvant chemoradiotherapy (nCRT) for locally advanced rectal cancer may induce a pathological complete response (pCR) but increase surgical morbidity due to radiation‐induced fibrosis. In this study the association between pCR and postoperative surgical morbidity was investigated. Methods: Patients in the Netherlands with rectal cancer who underwent nCRT followed by total mesorectal excision between 2009 and 2017 were included. Data were stratified into patients who underwent resection with creation of a primary anastomosis and those who had a permanent stoma procedure. The association between pCR and postoperative morbidity was investigated in univariable and multivariable logistic regression analyses. Results: pCR was observed in 976 (12·2 per cent) of 8003 patients. In 3472 patients who had a primary anastomosis, the presence of pCR was significantly associated with surgical complications (122 of 443 (27·5 per cent) versus 598 of 3029 (19·7 per cent) in those without pCR) and anastomotic leak (35 of 443 (7·9 per cent) versus 173 of 3029 (5·7 per cent) respectively). Multivariable analysis also showed associations between pCR and surgical complications (adjusted odds ratio (OR) 1·53, 95 per cent c.i. 1·22 to 1·92) and pCR and anastomotic leak (adjusted OR 1·41, 1·03 to 2·05). Of 4531 patients with a permanent stoma, surgical complications were observed in 120 (22·5 per cent) of 533 patients with a pCR, compared with 798 (20·0 per cent) of 3998 patients with no pCR (adjusted OR 1·17, 0·94 to 1·46). Conclusion: Patients with a pCR in whom an anastomosis was created were at increased risk of developing an anastomotic leak. Abstract : This study aimed to clarify the relationship between pathological response to neoadjuvant chemoradiotherapy and surgical complications. To do this, surgical complication rates were investigated in a nationwide population‐based study. More leaks Abstract : Antecedentes: La quimiorradioterapia neoadyuvante ( neoadjuvant chemoradiotherapy, nCRT) para el cáncer de recto localmente avanzado puede inducir una respuesta patológica completa ( pathological complete response, pCR), pero también puede aumentar la morbilidad quirúrgica debido a la fibrosis inducida por la radiación. En este estudio se investigó la asociación entre pCR y morbilidad quirúrgica postoperatoria. Métodos: Se incluyeron los pacientes con cáncer de recto que recibieron nCRT seguida de resección total del mesorrecto entre 2009 y 2017 en los Países Bajos. Los datos se estratificaron en pacientes en los que se realizó una resección con anastomosis primaria y en los que se realizó una resección con estoma permanente. La asociación entre pCR y morbilidad postoperatoria se investigó mediante análisis de regresión logística univariable y multivariable. Resultados: Se observó una pCR en 976 (12, 2%) de 8.003 pacientes. En el grupo de pacientes con anastomosis primaria ( n = 3472), la presencia de pCR se asoció significativamente con complicaciones quirúrgicas ( n = 122; 27, 5% versus n = 598; 19, 7% sin pCR) y fuga anastomótica ( n = 35; 7, 9 % versus n = 173; 5, 7% sin pCR). Las asociaciones entre la pCR y las complicaciones quirúrgicas y la pCR y la fuga anastomótica también se confirmaron en los análisis multivariables (razón de oportunidades ajustada, odds ratio, OR ajustado: 1, 53; i.c. del 95%: 1, 22‐1, 92; OR ajustado: 1, 41; i.c. del 95%: 1, 03‐2, 05, respectivamente). En el grupo con estoma permanente ( n = 4.531), se observaron complicaciones quirúrgicas en 120 pacientes (22, 5%) en los casos con presencia de pCR en comparación con 798 pacientes (20%) en ausencia de pCR (OR ajustado: 1, 17; i.c. del 95%: 0, 94‐1, 46). Conclusión: Los pacientes con pCR en los que se realizó una anastomosis tenían mayor riesgo de presentar una fuga anastomótica.